La motivación intrínseca potencia el desarrollo profesional en estudiantes de comunicaciones: un estudio correlacional - Rojas Virijivich, Rodolfo (2026)
In the Peruvian educational context, understanding the factors that influence students’ academic motivation and professional expectations is essential to optimize higher education and strengthen employability. The objective of this study was to analyze the relationship between academic motivation and professional expectations in communication students from a private institute in Lima, Peru. A quantitative, correlational, and non-experimental design was applied to a sample of 286 advertising science students, using two questionnaires as research instruments. These instruments measured extrinsic academic motivations, intrinsic academic motivations, as well as perceptions of job security and professional development. The results revealed positive and significant correlations, particularly between intrinsic motivation and professional development (Rho = .659) and between intrinsic motivation and job security (Rho = .472). Extrinsic motivation also showed positive correlations, although of lower magnitude (Rho = .395 and Rho = .359, respectively). It is concluded that intrinsic motivation is a key predictor of professional expectations, reinforcing the importance of promoting it within educational settings. This study contributes to the understanding of the link between motivation and expectations in Latin American contexts, opening the possibility of designing resources for educators in the discipline that may help motivate their students in a more comprehensive way, thereby fostering both academic persistence and a more effective and sustainable insertion into the labor market over time.